The Depiction of Cultural Identity and Cultural Assimilation in Gish Jen's Mona in the Promised Land - Hornychová, Aneta (Univerzita Pardubice, 2024)
This bachelor thesis explores the theme of identity and assimilation in the novel Mona in the Promised Land by Chinese-American author Gish Jen. It mainly focuses on the main character, Mona, who cannot find her true identity because she is both Chinese and American. Overall, the work deals with the search for true identity, whether religious or cultural and the obstacles that come with this process.
Znázornění kulturní identity a asimilace v románu Mona in the Promised Land od autorky Gish Jenové
Keywords: identita; asimilace; imigrace; náboženství; americko-čínská literatura; Jen, Gish; identity; assimilation; immigration; religion; Chinese-American literature; Jen, Gish